Analysis Of The Implementation Of The Sabtu Budaya Program On The Enhancement Of Students' Patriotism Character In Elementary Schools - Maulana, Arman; Sopani, Elza Maulia; Zain, A. Farmozi; Sumardi, Lalu (PT Rizkarya Cendekia Pustaka, 2025)
This study aims to analyze the implementation of the Sabtu Budaya (Cultural Saturday) Program and its impact on the development of patriotism among students class V at SDN 2 Jurit. This program is an initiative by the Education and Culture Office of West Nusa Tenggara Province to strengthen character education based on local culture. The research employed a descriptive qualitative method using observation, interviews, and questionnaires. The results show that the Sabtu Budaya activities are carried out regularly every third Saturday of the month, including: wearing traditional clothing, singing national and regional songs, organizing traditional games competitions, learning regional dances, screening and discussing nationalism-themed films, and conducting school environment clean-up through mutual cooperation. These six activities have successfully shaped students’ sense of nationalism, responsibility, and pride in local culture. A total of 97% of students responded “very good” to the program. Thus, Sabtu Budaya has proven to be an effective medium for instilling the value of patriotism through a contextual and enjoyable approach